Endoscopic resection of the submandibular gland: a new surgical approach - Karn, Sumeet; Pandit, Archit (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Submandibular gland excision is traditionally performed by the transcervical approach. To avoid or reduce visible scarring and nerve injury, diverse innovative surgical trials have been reported. Here we report a patient who had an endoscopic submandibular gland resection via a hairline incision. Methods: A 36-year-old woman presented with a right submandibular gland tumor that was found on a routine check-up. The submandibular gland was resected under endoscopic assistance via a posterior hairline incision using an ultrasonic scalpel. Results: The resection was successful, causing no acute complications, such as neural injury, hematoma, or seroma formation. The incision scar healed with an excellent cosmetic result. Conclusions: Endoscopic submandibular gland resection via a hairline incision was feasible and resulted in an excellent surgical and cosmetic outcome.